The Genetic Diversity of Cranberry Crop Wild Relatives, Vaccinium macrocarpon Aiton and V. oxycoccos L., in the US, with Special Emphasis on National Forests - Lorraine Rodriguez-Bonilla; Karen A. Williams; Fabian Rodríguez Bonilla; Daniel Matusinec; Andrew Maule; Kevin Coe; Eric Wiesman; Luis Diaz-Garcia; Juan Zalapa (Plants, 2020)
Knowledge of the genetic diversity in populations of crop wild relatives (CWR) can inform effective strategies for their conservation and facilitate utilization to solve agricultural challenges. Two crop wild relatives of the cultivated cranberry are widely distributed in the US. We studied 21 populations of Vaccinium macrocarpon Aiton and 24 populations of Vaccinium oxycoccos L. across much of their native ranges in the US using 32 simple sequence repeat (SSR) markers. We observed high levels of heterozygosity for both species across populations with private alleles ranging from 0 to 26. For V. macrocarpon, we found a total of 613 alleles and high levels of heterozygosity (HO = 0.99, HT = 0.75). We also observed high numbers of alleles (881) and levels of heterozygosity (HO = 0.71, HT = 0.80) in V. oxycoccos (4x). Our genetic analyses confirmed the field identification of a native population of V. macrocarpon on the Okanogan-Wenatchee National Forest in the state of Washington, far outside the previously reported range for the species. Our results will help to inform efforts of the United States Department of Agriculture Agricultural Research Service (USDA-ARS) and the United States Forest Service (USFS) to conserve the most diverse and unique wild cranberry populations through ex situ preservation of germplasm and in situ conservation in designated sites on National Forests.